Effects of macroporous adsorption resin on antibiotic resistance genes and the bacterial community during composting. (January 2020) - Bao, Jianfeng; Wang, Xiaojuan; Gu, Jie; Dai, Xiaoxia; Zhang, Kaiyu; Wang, Qianzhi; Ma, Jiyue; Peng, Huiling
Highlights: MAR improved the efficiency of reducing the relative abundances of ARGs and MGEs. MGEs were mainly responsible for the changes in the abundances of ARGs. ARGs and MGEs have the same potential host bacteria. MAR added at 5% can reduce the risk of ARGs in swine manure composting. Abstract: Swine manure is considered a reservoir for antibiotic resistance genes (ARGs), which may enter the soil and then the food chain to endanger human health. This study investigated the effects of adding 0%, 5%, and 15% (w/w) macroporous adsorption resin (MAR) on ARGs and the bacterial community during composting. The results showed that the addition of MAR reduced the abundances of ARGs (14.14–99.44%) and mobile genetic elements (MGEs) (47.83–99.48%) after swine manure composting. Significant positive correlations were detected between ARGs and MGEs, and thus the variations in MGEs may have led to the changes in ARGs. Redundancy analysis showed that MGEs had stronger effects on ARGs than environmental factors and the bacterial community. Network analysis suggested that ARGs and MGEs co-existed in common host bacteria. In conclusion, the results showed that adding 5% MAR can reduce the risk of ARG transmission.